INNOVATIONS IN PRESCHOOL EDUCATION: THE CONDITIONS OF EFFICIENCY OF INNOVATIVE PEDAGOGICAL PROCESSES - Oleksandra Lysenko; Bohdana Ivasyk (Vasyl Stefanyk Precarpathian National University, 2018)
The article deals with the concept of innovation. The purpose of the use of innovative technologies in education is analyzed. Their effectiveness in the educational process is proved. The author shows that innovative pedagogical technologies as a principle of pedagogy provide conditions for the development of the individual, the exercise of his right to individual creative input, personal initiative, freedom of self-development.It is proved that Innovative pedagogical technologies are one of the dominant tendencies of human development.The author emphasizes that the aim of innovation is to optimize the educational process, to ensure its compliance with the conditions and trends of social life. Innovation is not and can not be an end in pedagogical practice. It is precisely in this plane that the problem of the effectiveness of innovative pedagogical processes arises. For rational management of innovations it is necessary to know the prerequisites of their effectiveness, that is, factors that promote or restrain their effective flow and development. Effectiveness is interpreted as the ratio of the results of the action and the cost of their achievement. This means that even the highest under certain conditions, the result does not yet indicate the maximum effectiveness of the activity. It is necessary to take into account what resources and resources have been spent to achieve it. For example, if two technologies for teaching children of mathematics provide approximately the same level of mastering, then the one that needs the least effort will be more effective. But it is only possible to argue about more or less effective action when their goal is achieved.Thus, the effectiveness of the innovation depends on the beneficial effect achieved, the duration of the use of innovative technology, the cost of its implementation.In general, any innovation process in terms of its effectiveness is largely risky. The essence is not only in the potential of the effectiveness of the innovative idea, but also in many factors that influence the introduction and use of innovative pedagogical technology. Some of these factors are universal and are manifested in any field of human activity, others are common in the pedagogical environment. Key words: innovation, innovative education, training, teacher education.